1998
DOI: 10.1143/jjap.37.6841
|View full text |Cite
|
Sign up to set email alerts
|

High Transmittance SiC Membrane Prepared by Electron Cyclotron Resonance Plasma Chemical Vapor Deposition in Combination with Rapid Thermal Annealing

Abstract: The state-selective dissociation dynamics for anionic and excited neutral fragments of gaseous SiCl 4 following Cl 2p and Si 2p core-level excitations were characterized by combining measurements of the photoninduced anionic dissociation, x-ray absorption and UV/visible dispersed fluorescence. The transitions of core electrons to high Rydberg states/doubly excited states in the vicinity of both Si 2p and Cl 2p ionization thresholds of gaseous SiCl 4 lead to a remarkably enhanced production of anionic, Si − and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…8 Microcrystalline SiC alloys deposited by electron-cyclotron-resonance chemical-vapor deposition ͑ECRCVD͒ were utilized as carrier injection layers to improve the performance of a-SiC:H LEDs. 8 Recent research work 9,10 in ECRCVD SiC coating technology has demonstrated the potential for fabricating high-quality SiC x-ray mask membranes. Furthermore, the microstructure of SiC films on Si deposited by the ECRCVD technique was found to be an amorphous matrix embedded with nanosized crystalline particles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Microcrystalline SiC alloys deposited by electron-cyclotron-resonance chemical-vapor deposition ͑ECRCVD͒ were utilized as carrier injection layers to improve the performance of a-SiC:H LEDs. 8 Recent research work 9,10 in ECRCVD SiC coating technology has demonstrated the potential for fabricating high-quality SiC x-ray mask membranes. Furthermore, the microstructure of SiC films on Si deposited by the ECRCVD technique was found to be an amorphous matrix embedded with nanosized crystalline particles.…”
mentioning
confidence: 99%
“…Furthermore, the microstructure of SiC films on Si deposited by the ECRCVD technique was found to be an amorphous matrix embedded with nanosized crystalline particles. 9,10 On the other hand, obviously inspired by the discovery of porous Si emitting strong luminescence, some groups reported PL and EL spectra of porous SiC fabricated using single-crystal SiC polytypes such as 3C, 4H, and 6H. [11][12][13][14] However, there has been little work on the luminescence properties of nanocrystalline SiC films deposited on Si using the ECRCVD technique.…”
mentioning
confidence: 99%